Discourse segmentation and the management of multiple tasks in single episodes of air traffic controller-pilot spoken radio communication - Paul A. Falzon (Discours)
Episodes of VHF radio-mediated pilot-controller spoken communication in which multiple tasks are conducted are engendered in and through the skilful deployment and combination, by the parties to the talk, of multiple orders of discourse segmentation. These orders of segmentation are manifest at the levels of transmission design and sequential organisation. Both of these features are analysed from a Conversation Analytic standpoint in order to track their segment by segment genesis, development and completion. From the analysis it emerges that in addition to the serial type of sequential organisations described by Schegloff (1986), there exists an alternative form of organisation that enables tasks to be managed in a quasi-parallel manner, and which affords controllers and pilots a number of practical advantages in the conduct of their radio-mediated service encounters.